A Novel Three-Dimensional Glioma Blood-Brain Barrier Model for High-Throughput Testing of Tumoricidal Capability - Sherman, Hilary; Rossi, Ann E. (Frontiers in Oncology, 2019)
The blood-brain barrier (BBB) limits passage of substances between general circulation and the brain extracellular fluid, maintaining homeostasis in neural tissues and providing a defense against potential toxins. However, the protection provided by the BBB often prevents conventional chemotherapeutics from reaching brain tumors which makes brain cancers one of the most difficult cancers to treat (1). Traditionally, high-throughput testing of compound permeability through the BBB in vitro has been limited to assay of radio- or fluorophore-labeled compounds as they pass a cell monolayer growing on a permeable support system. Unfortunately, the labels themselves may negatively impact the assay, and the ability to determine resulting tumor cytotoxicity must be studied independently. The present study demonstrates proof-of-concept of a three-dimensional (3D) model to study label-free BBB transport as well as the resulting brain tumor cytotoxicity by combining two commercially available products: Corning® HTS Transwell®-96 tissue culture system and Corning 96-well spheroid microplates. Transwells are permeable support systems commonly used for drug transport and migration/invasion studies (2, 3). Corning spheroid microplates are cell culture microplates with round well-bottom geometry coated with Corning Ultra-low Attachment surface, enabling the formation of a single multicellular tumor spheroid centered in each well in a highly reproducible manner. By replacing the standard flat-bottom Transwell receiver plate with a Corning spheroid microplate, the resulting system — which can be tailored to any number of cell types and screening applications — enables a more comprehensive assay to study drug transport across the BBB and the resulting 3D glioma spheroid toxicity in an easy-to-use 3D high-throughput assay.